On joint effects of return policy coordination and retail competition - Son, Joong Y.; Enstroem, Rickard (My University, 2020)
This paper studies the effectiveness of a return policy as an incentive-aligned coordination mechanism in a decentralised supply chain for short life-cycle products. System performance with regards to profitability and product availability is assessed with a coordinated return policy between the vendor and two competing retailers. Building on the optimal return policy coordination model for short life-cycle products, this paper evaluates individual and joint effects of competition and coordination under the four different settings of competition with and without coordination, and no competition with and without coordination. Results indicate that joint effects are largely contingent on demand structures in the supply chain, whereas individually, return policy coordination displays greater effectiveness in improving fill rates at local retailers by maintaining high stocking levels and competition commands significant impact in improving the system profitability and service level by creating inventory pooling effects between competing retailers.
Keywords: supply chain coordination; retail competition; return policy; simulation